Etika Bisnis Islam dalam Pencegahan Praktik Monopoli UMKM Fashion Muslim - David Abdul Azis Al Hamid; Romi Faslah (CV. ITTC INDONESIA, 2025)
Monopolistic practices in business pose significant challenges to creating fair and healthy markets. This study examines monopolyfrom Indonesian positive law and Islamic law perspectives, exploring how Islamic business ethics can serve as alternative solutions for fostering just business environments. Using descriptive qualitative approach, this research presents a case study of Muslim fashion MSMEs in Pulau Mentaro Village, Muaro Jambi. Findings indicate that applying justice, honesty, and collaboration values among small-scale entrepreneurs promotes healthy competition and prevents monopolistic behavior. Islamic business ethics principles prove relevant for broader application, including national business levels. The case study reveals 18 MSMEs in Pulau Mentaro successfully prevented monopolistic practices through Islamic principles implementation: justice ('adl) in fair pricing, honesty (amanah) in transparency, cooperation (ta'awun) in mutual support, and social responsibility in community empowerment. All MSMEs experienced stable revenue growth, demonstrating Islamic business ethics can encourage inclusive and sustainable economic development.